The social in scene in significant materiality - doi: 10.4025/actascilangcult.v32i2.11759 - Lagazzi, Suzy (Acta Scientiarum. Language and Culture, 2010)
This paper analyses the movies: Tropa de Elite, Tereza and Boca de Lixo, with the aim of providing visibility, in the imbrication of different significant materialities, for the discursive work of textualizing social differences. In the theoretical and methodological perspective of the materialistic Discourse Analysis, this text allows us to observe the functioning of the contradiction during the oppositional naturalization that structures most of the relations which organize our society, presenting the resistance as a process of possible displacement